Workplace Violence: A Survey of Nationally Registered Emergency Medical Services Professionals. (28th May 2015) - Oliver, Anthony; Levine, Roger
Abstract : Previous studies on violence against prehospital personnel have mainly reported on "verbal" and "physical" violence. This study explored how provider demographic and work-related characteristics were associated with five different forms of workplace violence (being cursed or threatened; being punched, slapped, or scratched; being spat upon; being stabbed/stabbing attempt; and being shot/shooting attempt). A cohort of nationally registered United States Emergency Medical Services professionals was surveyed to determine the experience of each of these types of patient initiated violence by these providers and their partners. Multivariable logistic regression analyses indicated gender was significantly associated with both being cursed/threatened and being stabbed or experiencing a stabbing attempt (odds ratio (OR) = 0.65, CI = 0.44–0.96; OR = 0.27, CI = 0.09–0.75, resp.). Level of EMT practice was significantly associated with being cursed/threatened, being spat upon, and being punched, slapped, or scratched (OR = 0.17, CI = 0.11–0.27; OR = 0.30, CI = 0.21–0.43; OR = 0.31, CI = 0.22–0.44, resp.). Both community size and experience were significantly associated with all the types of violence investigated. EMS workplace violence research is at its infancy; thus this study adds to a limited but growing body of knowledge.